High room temperature ferromagnetic moment of Ho substituted nanocrystalline BiFeO3 - Thakuria, Pankaj; Joy, Pattayil Alias (Applied Physics Letters, 2010)
Magnetic properties of trivalent rare-earth ion substituted nanocrystalline BiFeO3 have been studied for the compositions Bi0.875R0.125FeO3 (R=La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, and Yb). All compositions show ferromagnetic characteristics at room temperature, with enhanced magnetization after substitution. Very high magnetization (at 6 T), almost three times that of the unsubstituted composition, is observed for R=Ho, and highest remnant magnetization is obtained for R=Nd and Sm. The magnetic transition temperature is increased by similar to 20 K for R=La. The results show that it is possible to tune the magnetic characteristics of the nanocrystalline multiferroic BiFeO3 by the choice of the rare-earth ion. (C) 2010 American Institute of Physics. [doi: 10.1063/1.3502481]